Impact of Environmental, Social and Governance Factors on Investment Decision of Investors in Nepal - Karmacharya, Bibek (Journal of Nepalese Business Studies, 2023)
In recent years, there has been a growing emphasis on the impact of Environmental, Social, and Governance (ESG) factors in investment decision-making. This study explores the relationship between ESG factors and investment decisions, focusing on 392 individual investors in Pokhara, Nepal. A survey-based research design was employed, analyzing data through Confirmatory Factor Analysis and path analysis. The results indicated a significant positive impact of social and governance variables on investment decisions, whereas environmental factors showed no significant influence. Investor awareness was found to moderate the relationship between governance factors and investment decisions, emphasizing its importance. The independent variables explained approximately 69 percent of the variation in investment decisions. The study's findings underscore the significance of ESG factors in guiding investment decisions. This research offers valuable insights for brokerage houses and companies, facilitating the development of investment products tailored to individual investors' ESG preferences. These efforts contribute to promoting sustainable investment practices in Nepal.